2021
DOI: 10.3390/molecules26237304
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Identification of Antimicrobial Peptides from Medicinal Seeds

Abstract: Traditional medicinal plants contain a variety of bioactive natural products including cysteine-rich (Cys-rich) antimicrobial peptides (AMPs). Cys-rich AMPs are often crosslinked by multiple disulfide bonds which increase their resistance to chemical and enzymatic degradation. However, this class of molecules is relatively underexplored. Herein, in silico analysis predicted 80–100 Cys-rich AMPs per species from three edible traditional medicinal plants: Linum usitatissimum (flax), Trifolium pratense (red clove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Other proteomic studies identified novel proteins/peptides of medicinal plant origin with pharmacological interests (Figure 3, grey part) (Moyer et al, 2021b). For instance, seven novel peptides belonging to three antimicrobial peptide classes, including lipid transfer proteins, snakins and a defensin, were identified by MSbased peptidomics analysis from the aerial tissues of edible amaranth (Amaranthus tricolor) plants (Moyer et al, 2021a).…”
Section: Figurementioning
confidence: 99%
“…Other proteomic studies identified novel proteins/peptides of medicinal plant origin with pharmacological interests (Figure 3, grey part) (Moyer et al, 2021b). For instance, seven novel peptides belonging to three antimicrobial peptide classes, including lipid transfer proteins, snakins and a defensin, were identified by MSbased peptidomics analysis from the aerial tissues of edible amaranth (Amaranthus tricolor) plants (Moyer et al, 2021a).…”
Section: Figurementioning
confidence: 99%
“…Regarding selectivity and recovery, affinity chromatography methods are the most effective downstream processing techniques at the moment (Vollet Marson et al, 2020). Further identification of the peptide can be achieved using mass spectrometry (Moyer et al, 2021) and combination methods (tandem mass spectrometry in combination with LC-MS) (Zhang et al, 2022).…”
Section: Identification and Analyses Of Ppdpmentioning
confidence: 99%
“…Other proteomic studies identified novel proteins/peptides of medicinal plant origin with pharmacological interests ( Figure 3 , grey part) ( Moyer et al., 2021b ). For instance, seven novel peptides belonging to three antimicrobial peptide classes, including lipid transfer proteins, snakins and a defensin, were identified by MS-based peptidomics analysis from the aerial tissues of edible amaranth ( Amaranthus tricolor ) plants ( Moyer et al., 2021a ).…”
Section: Proteomic Dissection Of Medicinal Plants In Different Manner...mentioning
confidence: 99%